2022
DOI: 10.1093/jacamr/dlac054
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in commensal Escherichia coli from humans and chickens in the Mekong Delta of Vietnam is driven by antimicrobial usage and potential cross-species transmission

Abstract: Objectives To investigate phenotypic antimicrobial resistance (AMR) in relation to antimicrobial use (AMU) and potential inter-species transmission among Escherichia coli from humans and chickens located in the same households in the Mekong Delta of Vietnam. Methods We collected data on AMU and faecal swabs from humans (N = 426) and chickens (N = 237) from 237 small-scale farms. From each sample, one E. coli strain was isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The high AMR levels could be stemmed from the transfer of AMR bacteria and AMR-encoding genes due to close contact between humans, animals and the environment [ 117 ]. A recent One Health study in Vietnam reported a high similarity in AMR profiles of E. coli from humans and chickens from the same farms higher than those from different farms implying the potential transmission of cross-species [ 118 ]. Furthermore, the presence of bacterial isolates resistant to antimicrobials commonly administered to humans and animals from wastewater has been demonstrated in Vietnam [ 71 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high AMR levels could be stemmed from the transfer of AMR bacteria and AMR-encoding genes due to close contact between humans, animals and the environment [ 117 ]. A recent One Health study in Vietnam reported a high similarity in AMR profiles of E. coli from humans and chickens from the same farms higher than those from different farms implying the potential transmission of cross-species [ 118 ]. Furthermore, the presence of bacterial isolates resistant to antimicrobials commonly administered to humans and animals from wastewater has been demonstrated in Vietnam [ 71 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that higher population and animal production densities are correlated with AMU and AMR [ 124 ]. Recent studies demonstrated to a high-level detail amounts of antimicrobials used in human and chicken production systems in the south of Vietnam [ [7] , [125] , 118 ]. However, there is an existing gap in AMU studies in the northern region.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to antimicrobials of various groups can lead to cross-resistance, and the antibiotic resistance genes may spread among bacteria through horizontal gene transfer (HGT). That is, the antimicrobial resistance of commensal bacteria, such as Escherichia coli , is equally important as they constitute a reservoir and vector of resistance [ 3 , 4 ]. When E. coli bacteria are in the presence of antibiotic pressure, they are forced to develop alternative ways to survive and grow in a harmful environment.…”
Section: Introductionmentioning
confidence: 99%
“…The misuse and overuse of antibiotics in aquaculture, livestock, and humans might be contributed to the development and dissemination of antimicrobial resistance (AMR) in Vietnam in particular and over the world in general. Furthermore, the high prevalence of E. coli isolates produces extended-spectrum β-lactamase (ESBL) in the food chain exposing a major threat to public health since fewer available antibiotics for the treatment of Enterobacteriaceae infection [ 8 ]. Thus, how to monitor the AMR in the food chain is urgent to provide safe and high-quality food for consumers.…”
Section: Introductionmentioning
confidence: 99%